Genetic abnormalities in thyroid hormone deiodinases. Issue 5 (October 2015) - Taylor, Peter N.; Peeters, Robin; Dayan, Colin M.
Abstract : Purpose of review: The purpose of this study was to review several of the most recent and most important clinical studies regarding the effects of how genetic variation in the deiodinases can influence health. Recent findings: Common variation in DIO1 but not DIO2 or DIO3 is robustly associated with thyroid hormone levels at genome-wide levels of significance although the effect is modest. There is growing evidence that common variation in DIO2, particularly the Thr92Ala substitution, is associated with important clinical endpoints including osteo-arthritis and intelligence quotient; however, the mechanism of action appears to vary between tissues with several unexpected pathways recently being elucidated including effects on Golgi function and DNA methylation. In addition, there is emerging evidence of interaction with iodine and thyroid status. Summary: The clinical importance of genetic variation in the deiodinases has yet to be fully elucidated and their impact is likely to vary between individuals and body systems dependent on multiple factors within tissues and coexistent diseases and environmental factors. Exploration of whether there are rare functional variants in the deiodinases is now possible in population studies, which may yield greater insight in the near future. Studies of the impact of genetic variation in the deiodinases in individuals with iodine deficiency, subclinical thyroid disease, or those on levothyroxine are urgently needed.